Perwilayahan Pariwisata Di Kabupaten Semarang Dengan Model Titik Pusat - Titi Ariyati; Hadi Wahyono (Jurusan Perencanaan Wilayah dan Kota, 2016)
Tourism uniqueness and diversity in a region affect tourism development of that region. One of the suitable developing strategy for a region which has a lot of tourist attractions is a tourism regionalization. Tourism regionalization means dividing tourism regions which has potential, and then make it into a tourism destination. Tourist attraction in Semarang Regency can be classified into 8 types which is nature, cultural, historical, man made, pilgrim, industrial, sports, and culinary. This research aims to describe tourism potential of Semarang Regency and arrange tourism regions with Mean Centre Model as one of developing strategy in Semarang Regency. Tourism regionalization expected to improve all of the tourism potential in order to make them developing together. The research question is how the tourism potential in Semarang Regency and how to develop them based on tourism regionalization which is suitable for tourism in Semarang Regency to make it develop optimally?. Regionalization can be done by reviewing types and potential level of tourist attraction, deciding tourist attraction hierarchy, and arrange tourism regionalization with Mean Centre Model. Methods in this research are Delphi method and Mean Centre method. Delphi method used to decide types, potential level, and hierarchy of tourist attraction. Mean Centre method used to determine mean centre as a reference of tourism regionalization. Tourism regionalization arrangement in Semarang Regency aims to give input about developing tourism strategy in Semarang Regency in order to make it developed optimally.